Digitalisasi Bahan Ajar Untuk Membangun Pemahaman Agama Islam Yang Moderat - Lestari, Agus; Handoko, Yudo (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
This research aims to analyze the utilization of the digitalization of teaching materials for the Islamic religion course in enhancing moderate understanding of Islam among students in the Society 5.0. In this scientific paper, the author discusses the digitalization of teaching materials for the Islamic religion course to improve moderate understanding of Islam in the Society 5.0 with a qualitative research approach. In this approach, The author collected data and information through interviews, observations, and various sources related to the topic, including scientific journals, books, and reliable online sources. The results of the study show that digitalization of teaching materials can help improve moderate understanding of Islam among students. However, there are still several obstacles in implementing digitalization of teaching materials, such as the digital divide and lack of direct interaction between lecturers and students. Therefore, educational institutions need to provide adequate internet access and devices, technology skills training, provide online and offline discussion forums, and introduce anti-plagiarism policies to overcome these obstacles. This research contributes to the development of digital technology in Islamic education in the Society 5.0.